Resolución pacífica de conflictos - Vega Ortega, María Nancy (2017)
The present research is related to "THE EFFECTIVENESS OF THE CODE OF INSTITUTIONAL COEXISTENCE IN THE PEACEFUL RESOLUTION OF CONFLICTS," and aims to achieve positive and harmonious coexistence in the educational community. For this, it was emphasized everything related to the information of the educational establishment, the search for the information of the scientific content, which allowed us to know everything that was needed for the investigation, raised the problem with bases, used methods which helped In describing the project according to the school need, in the same way the collection of information was investigated with surveys to the director, teachers, students and parents, where each one provided real and true facts of the problem that occurs in the institution, East was done through the selection of students in the fourth, fifth, sixth and seventh levels of basic education who helped me at work, the technique that was developed was the survey, the instrument: the questionnaire, these facilitated the work that was indispensable in order to create the content....